Analisis Menentukan Harga Jual Produk Minuman Dan Snack Café Komunikopi Sampang Madura - Ach. Sholahur Robany (Student Research Journal, 2023)
This study aims to determine the calculation of the cost of goods produced and the profit or not of the results of product sales. In the title of the thesis "Analysis of Determining the Selling Price of Beverage and Snack products at the Komunikopi Cafe Sampang Madura", the method used in this study is a descriptive approach. The data analysis used is by collecting and clarifying data relevant to the problem studied in this study, namely analyzing the purchase price of komunikopi café products then analyzing the calculation of the selling price of the product and analyzing the calculation of the selling price of the product in accordance with the provisions. The results of the overall study are the selling price set by the komunikopi café using the relative selling price method whose selling price follows the selling price in the market that has been set by cafes in the sampang regency area. Related to the calculation of costs at this company is still inadequate so that the cost calculation follows the selling price that relativ is used in cafes in the Sampang Madura area.